Responsibility of Panitikismo in the Management and Utilization of Sultanate Land in Gunungkidul Regency - Ramadhanty, Diva Azmia; Yunanto, Yunanto (Jurnal Daulat Hukum, 2024)
Panitikismo is a customary institution of the Palace that is authorized to take care of the management and utilization of Sultanate Land. The purpose of this study is to analyze how Panitiksimo's legal and non-legal responsibilities in the management and utilization of Sultanate Land in Gunungkidul Regency and analyze what efforts Panitikismo has made in overcoming violations that occur against the use of Sultanate Land. This research uses qualitative research, using a sociological juridical approach. The data sources used are primary, secondary, and tertiary legal materials. Data collection methods using observation, interviews, documentation, and questionnaires to related communities. Data validity is carried out using triangulation techniques. The results of this study show that the legal and non-legal responsibilities that have been carried out by Panitikismo are carrying out responsibilities such as registering the Sultanate Land to the National Land Agency, providing compensation when things happen that are not in accordance with the agreed agreement, and providing education to the public regarding how to apply for a permit to use the Sultanate Land, this is strengthened by the theory of legal responsibility. Panitikismo's efforts in overcoming violations in the use of Sultanate Land are such as monitoring and controlling the use of Sultanate Land and conducting periodic monitoring according to the mandate it has received. The conclusion of this research is that Panitikismo has carried out its responsibilities well in accordance with the theory of legal responsibility, namely carrying out its obligations to register Sultanate Land and provide socialization to the public regarding the importance of applying for a serat kekancingan permit.